Adoption of services and apps on mobile phones by micro-entrepreneurs in Sub-Saharan Africa. (January 2021) - Paas, Leonard J; Eijdenberg, Emiel L; Masurel, Enno
This article shows that acquisition pattern analysis is highly suited for research in developing economies. Consumers in such contexts prioritize the adoption of alternative product-services as a result of resource constraints. In the reported acquisition pattern analysis, we provide insights into sequential adoption of services and applications (apps) on mobile phones, for example, Facebook and mobile money, by micro-entrepreneurs in Sub-Saharan Africa. We collected survey data from 169 Zambian food vendors, and through Mokken scale analysis we derived an acquisition pattern for 12 analyzed services and apps. Micro-entrepreneurs with more employees, tertiary education, and who were younger tended to be closer to the hierarchy's apex. These findings imply that the individual's mobile phone technology maturity and business development drive their adoption of services and apps. After presenting these results, we conclude with a discussion of the theoretical insights, managerial insights, and implications for policy makers resulting from the study.